Functionalized cardiovascular stents - Wall, J. Gerard; Podbielska, Halina; Wawrzynska, Magdalena (Woodhead Publishing series in biomaterials., 2017)
Cardiovascular disease is a major cause of mortality in the western world and about half of these deaths are caused by coronary artery disease. One of the most commonly used interventions to treat arterial blockages is to deploy an arterial stent to keep the vessel open. Traditionally, some cardiovascular stents have been associated with serious side-effects, such as thrombosis. This book describes the fundamentals of cardiovascular stents, technologies to functionalize their surfaces and the market status of these important implants. The chapters provide specific focus on the production and evolution of cardiovascular stents, providing essential knowledge for researchers on advances in the field and knowledge of how cardiovascular stents are currently being "functionalized" in order to improve their biocompatibility and minimize negative outcomes in vivo